PENYULUHAN HUKUM DAN PENINGKATAN KESADARAN MASYARAKAT DALAM PENGELOLAAN SAMPAH DI KELURAHAN SUNGAI PUTRI KOTA JAMBI - Ardian Kurniawan; Robi'atul Adawiyah; Anggi Purnama Harahap; Devrian Ali Putra; Rafikah Rafikah; Habibi Habibi (LPPM Universitas Al Muslim, 2023)
Garbage is one of the many environmental problems that exist today. The community and government in Jambi City face the same problem with the amount of waste volume increasing from time to time. Issuance of Perda Jambi City No. 5 of 2020 concerning Waste Management, it is hoped that public awareness of environmental cleanliness will improve. However, many people still don't know about this regional regulation, as well as the lack of socialization about how to manage waste properly. This activity was carried out as a form of community service in the form of socialization on how to manage waste and legal counseling related to regional regulations regarding waste management in Jambi City. Located in Sungai Putri Village, Danau Sipin District, Jambi City, this activity was generally carried out using interactive lecture and discussion methods. So, it is hoped that through this extension activity the paradigm and responsibility of the community for environmental cleanliness can be changed for the better, especially in waste management with an environmental perspective. In addition, by using the understanding approach through Islamic law, activity can be more targeted because the majority of residents who attend counseling are Muslims. Residents' concern for the cleanliness of their environment is in line with Islamic religious orders which are the essence of the material presented